Are Parents Patient? The Influence of Parenting Role Salience and Parental Status on Impatience - Li, Yuanyuan J.; Liu, Yuanyuan (Frontiers in Psychology, 2018)
In the classic intertemporal discounting task (Thaler, 1981), individuals always have to make trade-off decisions between smaller-sooner and larger-later monetary rewards. We explored how parental role salience influences individuals’ choice between smaller-sooner and larger-later choices. Parental role salience is both measured and manipulated in this research. Our results show a significant interaction between parental status and manipulated parental role salience. Specifically, we found that parents are more impatient than nonparents. Additionally, only among nonparents, manipulated parental role salience enhances impatience.